Childhood sexual abuse, sexual motives, and adolescent sexual risk-taking among males and females receiving child welfare services. (April 2017) - Wekerle, Christine; Goldstein, Abby L.; Tanaka, Masako; Tonmyr, Lil
Abstract: Childhood sexual abuse (CSA) is associated with multiple negative outcomes, including increased risky sexual behavior. To date, the majority of research on the relationship between CSA and risky sex in adolescence has been limited, with a lack of focus on males and youth receiving child welfare services. Participants in the current study were 297 youth (mean age = 15.98; SD = 1.01, 57.6% female) from the child welfare system who reported being sexually active at the time of the survey. CSA was associated with severity of other types of maltreatment for both genders, and exposure to intimate partner violence for females only. In general, males engaged in more sexual risk behaviors than females. Males with CSA had stronger motives to have sex for: (1) coping, (2) peer approval and (3) partner approval, as compared to non-CSA males; as well as (4) greater motives for partner and peer approval compared to females with CSA. Males with no CSA had stronger sexual motives for enhancement (e.g., feeling pleasure) compared to females with no CSA. Mediation analyses revealed a significant indirect effect for coping motives for males: CSA was associated with increased motives to use sex for coping which was associated with increased sexual risk-taking. These findings provide important information regarding the relationship between CSA and sexual risk-taking for child welfare sample and highlight coping with negative affect as a potential mechanism that underlies the CSA-risky sex relationship. It also encourages further consideration of motives for risk and resilience behaviors among youth.